2020
DOI: 10.1186/s12992-020-00624-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychological distress, fear and coping strategies during the COVID-19 pandemic in Australia

Abstract: Background The COVID-19 pandemic disrupted the personal, professional and social life of Australians with some people more impacted than others. Objectives This study aimed to identify factors associated with psychological distress, fear and coping strategies during the COVID-19 pandemic in Australia. Methods A cross-sectional online survey was conducted among residents in Australia, including patients, frontline health and other essential service workers, and community members during June 2020. Psychologi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
215
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(273 citation statements)
references
References 36 publications
44
215
11
3
Order By: Relevance
“…Other studies also found a negative impact of substance use on a psychological response, either in a form of association of alcohol intake with higher risk on reporting the burnout (Colville et al, 2017), or substance use with lower resilience that is highly correlated with anxiety, depression and perceived stress (Smith et al, 2008), and with increased anxiety (McPherson, 2003). Several studies showed negative effect of maladaptive coping styles on mental health during COVID-19 pandemic, associating it with higher anxiety and depression, higher level of psychological distress and lower wellbeing (Dawson & Golijani-Moghaddam, 2020;Rahman et al, 2020;Rettie & Daniels, 2020;Wang et al, 2020b;Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found a negative impact of substance use on a psychological response, either in a form of association of alcohol intake with higher risk on reporting the burnout (Colville et al, 2017), or substance use with lower resilience that is highly correlated with anxiety, depression and perceived stress (Smith et al, 2008), and with increased anxiety (McPherson, 2003). Several studies showed negative effect of maladaptive coping styles on mental health during COVID-19 pandemic, associating it with higher anxiety and depression, higher level of psychological distress and lower wellbeing (Dawson & Golijani-Moghaddam, 2020;Rahman et al, 2020;Rettie & Daniels, 2020;Wang et al, 2020b;Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been put forth to identify various sociodemographic factors, social and job-related factors (e.g., working as health care professions, poor household income and high social media exposure) and pre-existing psychiatric illnesses, which increased the risks of anxiety and depression during the COVID-19 pandemic [1,3,15]. In addition, there is a growing body of evidence addressing the interrelationships between the perceived threats related to COVID-19, coping strategies and mental health outcomes [16][17][18][19]. With the more use of emotional-focused coping [18,19], the less use of problem-focused coping [19] and the lower social support [18], people tend to exhibit more mental health symptoms, including symptoms of depression and anxiety [18,19].…”
Section: Psychological Flexibility and Prosocialitymentioning
confidence: 99%
“…An emerging body of research suggests that lockdown-related changes in addictive and compulsive behaviors may be predicted by, or otherwise related to, behavior-specific factors, such as motives [e.g., ( 13 )] and pre-existing severity ( 6 , 10 , 14 ). However, individual characteristics also play a role [e.g., ( 15 )]. This pattern of findings is not unique to COVID-19; there is a wealth of past research showing that while stressful life events generally increase risk for addictive and compulsive behaviors ( 16 19 ), the extent to which they do is influenced by individual differences ( 20 22 ).…”
Section: Introductionmentioning
confidence: 99%